The The Comparative Study between Using Factor Tree Technique and Tabular Technique in Determining Greatest Common Divisor (GCD) and Least Common Multiple (LCM) - Rifqi Silfiana (LP2M STAI Darul Kamal NW Lombok Timur, 2020)
Abstract The objectives of the research were to find out the profile of the students learning result using factor tree technique, to find out the profile of the students learning result using tabular technique, and to find out the difference between students learning result implementing factor tree technique and tabular technique in determining Greatest Common Divisor (GCD) and Least Common Multiple (LCM) at the 5th-grade students of MI Al Ma’arif Kebumen village, Banyubiru district, Semarang regency. This research was quantitative research with quasi-experiment design. The research population was 54 students. Its samples were 5th-grade students of A as the first experimental class while 5th-grade students of B as the second experimental class. The instruments were pre-test and post-test of the students learning result, and the observation sheet. The technique of data analysis was descriptive statistical analysis and inferential statistic. The research showed that in the first experimental class the mean of pre-test was 42,59 and the post-test mean was 60,96. Thus, in the second experimental class the pre-test mean was 41,15 and the post-test mean was 83. Based on the result of inferential analysis was tcount in the mount of 6,4787 and ttable as big as 2,6737 with 99% level of trustiness and 1% level of error, because tcount > ttable consequently H1 was accepted and H0 was rejected. It meant there was significant difference between students learning result using factor tree technique and tabular technique in determining Greatest Common Divisor (GCD) and Least Common Multiple (LCM) at the 5th-grade students of MI Al Ma’arif Kebumen village, Banyubiru district, Semarang regency.